Neurosensory Alterations in Retinopathy of Prematurity: A Window to Neurological Impairments Associated to Preterm Birth - Martina Lucchesi; Silvia Marracci; Rosario Amato; Luca Filippi; Maurizio Cammalleri; Massimo Dal Monte (Biomedicines, 2022)
Retinopathy of prematurity (ROP) is one of the main blinding diseases affecting preterm newborns and is classically considered a vascular disorder. The premature exposure to the extrauterine environment, which is hyperoxic in respect to the intrauterine environment, triggers a cascade of events leading to retinal ischemia which, in turn, makes the retina hypoxic thus setting off angiogenic processes. However, many children with a history of ROP show persistent vision impairment, and there is evidence of an association between ROP and neurosensory disabilities. This is not surprising given the strict relationship between neuronal function and an adequate blood supply. In the present work, we revised literature data evidencing to what extent ROP can be considered a neurodegenerative disease, also taking advantage from data obtained in preclinical models of ROP. The involvement of different retinal cell populations in triggering the neuronal damage in ROP was described along with the neurological outcomes associated to ROP. The situation of ROP in Italy was assessed as well.